Development of the Competence Measure of Individual Teacher-Student Relationships (COMMIT): Insight Into the Attitudes, Knowledge, and Self-Efficacy of Pre-service Teachers - Borremans, Liedewij F. N.; Spilt, Jantine L. (Frontiers in Education, 2022)
The importance of dyadic teacher-student relationships for both teachers and students is widely acknowledged. However, only limited research has explored how competent teachers feel in building these relationships. The current study aimed, first, to deepen the knowledge on relational competence by targeting teachers’ competence in building dyadic teacher-student relationships specifically. To this end, the Competence Measure of Individual Teacher-student relationships (COMMIT) was developed. This questionnaire is explicitly based on theories used in research on affective teacher-student relationships and addresses multiple aspects of competence (attitudes, knowledge and self-efficacy). Second, as teacher education programs have been repeatedly criticized for not sufficiently targeting relational competencies, the current study focused on pre-service teachers’ perceived competence and aimed to explore differences in this competence across pre-service teachers in subsequent years of their teacher training. Criterion validity of the newly developed COMMIT was examined in a sample of pre-service teachers in pre-primary and primary teacher education programs (N = 535). Six subscales were created, addressing pre-service teachers’ attitude towards teacher-student relationships (1 scale), their knowledge of teacher-student relationships and coping (2 scales), and their self-efficacy beliefs with regard to building closeness, coping with conflict, and reflective functioning (3 scales). Results showed that pre-service teachers had a rather positive attitude towards teacher-student relationships, and felt quite knowledgeable and self-efficacious, yet not in all aspects of dyadic relationship-building. Results further revealed that pre-service teachers in the final year of teacher training felt more competent, yet, again, not for all aspects of dyadic relationship-building. Notably, differences between pre-service teachers in subsequent years of teacher education were less pronounced in primary compared to pre- primary teacher education programs. Suggestions for future research and implications for initial teacher training are discussed.